Answer:
The graph of function f is shifted right 3 units and up 4 units.
Explanation:
Let f(x) be the parent function.
Rule : f(x)→f(x-b)
The graph shifts right by b units
So, shift the parent graph by 3 units
So, f(x)→f(x-3)
So, the graph shifted right by 3 units
Rule : f(x)→f(x)+b
The graph shifts up by b units
Now shift the obtained graph up by 4 units
So, f(x-3)→f(x-3)+4
So, the graph shifts up by 4 units
Thus Option D is correct.
The graph of function f is shifted right 3 units and up 4 units.
So, g(x) = f(x-3)+4
Thus